Personality Traits, Knowledge-Hiding Behavior and Job Performance of Employees - HANG, Nga Nguyen THI; KIM, Nam Nguyen (Foundations of management, 2025)
The banking sector is knowledge intensive and faces increasing competitive pressure. Knowledge hiding can undermine job performance and erode an organization’s competitive advantage. This study aims to examine the relationship between personality traits according to the Big Five model, knowledge-hiding behavior, and individual job performance in the context of the banking sector in Vietnam. The research employs a quantitative analysis approach using survey data from 226 banking employees, which was analyzed through structural equation modeling. The research results indicate that extraversion, agreeableness, and openness to experience personality traits have a negative relationship with knowledge-hiding behavior. Conscientiousness shows a positive relationship with knowledge-hiding behavior. The knowledge-hiding behavior of employees is found to decrease their job performance. This study makes a significant contribution to theoretical understanding by supplementing the knowledge management literature on the complex relationship between personality traits and knowledge-hiding behavior in the knowledge-intensive field. The research also aids knowledge management practitioners in gaining profound insights into the relationship between personality traits, knowledge hiding, and individual job performance, enabling practical applications in specific situations.